Income and Substitution Effects of Estate Taxation - Hines, James R (American Economic Review, 2013)
This paper evaluates the effect of estate taxes on labor supply. The analysis decomposes the effect of estate taxation into the substitution effect of relative price changes and the two income effects for which the estate tax is responsible. These two income effects arise from tax burdens on those who leave estates plus tax burdens on those who receive them. Despite the double income burden of the estate tax, existing empirical evidence suggests that the net effect of estate taxation on aggregate labor supply is uncertain.